2012
DOI: 10.1670/11-118
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Field Trip on the Attitude of Schoolchildren toward Unpopular Organisms: An Experience with Snakes

Abstract: International audienceThe general public prefers to support conservation projects that focus on a few, easily ''loveable'' species; consequently most of biodiversity is neglected. It is essential to redress such bias and to educate children about the value of a wide diversity of organisms, including those labeled by social bias as less appealing. Because snakes are among the most disliked animals, they are suitable candidates for such endeavor. We evaluated the impact of a single field trip on the attitudes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
80
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 44 publications
7
80
0
7
Order By: Relevance
“…In line with previous work, we here showed that disgust is lower after an intervention with living invertebrates. This is comparable with a study about snakes (Ballouard et al, 2012) and spiders, where Wagler and Wagler (2017) reported that a treatment group with exposure to living spiders exhibited a steady and maintained decrease in the levels of fear, perceived danger and disgust across the time. Concerning snails, snail disgust was significantly reduced by the treatment and this is comparable to another study where a lesson with living snails successfully reduced snail disgust in fifth-graders (Prokop and Fančovičová, 2016).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In line with previous work, we here showed that disgust is lower after an intervention with living invertebrates. This is comparable with a study about snakes (Ballouard et al, 2012) and spiders, where Wagler and Wagler (2017) reported that a treatment group with exposure to living spiders exhibited a steady and maintained decrease in the levels of fear, perceived danger and disgust across the time. Concerning snails, snail disgust was significantly reduced by the treatment and this is comparable to another study where a lesson with living snails successfully reduced snail disgust in fifth-graders (Prokop and Fančovičová, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Negative emotions, such as anxiety and disgust, are related to lower achievement (Randler et al, 2005) and less willingness to protect disgusting species (Prokop and Fančovičová, 2013), while positive emotions, like interest and well-being are positively related to learning achievement and motivation (Randler et al, 2012b). Disgust reactions are usually hard to unlearn (Kasperbauer, 2015), but studies in clinical settings on phobia (e.g., spider or snake phobia) showed that an intervention with living animals can reduce this phobia, lending support for these types of intervention (Ballouard et al, 2012).…”
mentioning
confidence: 99%
“…Direct interaction with live animals appears to be important as far as producing an attitude change (Morgan & Gramann, 1989;Ballouard et al, 2012). This is consistent with Kolb's Experiential Learning Cycle, which consists of four stages (Kolb, 1984).…”
Section: Introductionsupporting
confidence: 52%
“…Tomasek, Matthews, and Hall (2005) describe how to sample for reptiles and amphibians using a drift fence array and pitfall traps, and note that through amphibian and reptile sampling, student attitudes are altered, with the students becoming more environmentally aware and more appreciative of amphibians and reptiles (Tomasek et al, 2005). Ballouard, Provost, Barre, and Bonnet (2012) assert that field trips that incorporate hands-on experiences with animals are more impactful when it comes to altering student attitudes than the modern-day trend of providing virtual experiences. The authors used a single snake-catching field trip and some simple snake handling to positively impact the attitudes of 500 school children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation